Indonesian Consumers’ Repeat Purchase Behavior Of Green Innovative Fuel: An Extension Of Cognitive – Affective - Behavior Model - Widodo, Arry (2019)
Green products have become one of the most important strategic tools to achieve sustainable development in the industry due to popular environmental trends. Strict environmental regulations and popular environmentalism have been observed to change competitive rules resulting in the creation of green innovative fuels for consumers in the marketplace. This study attempts to explain the behavior of consumer repurchase of green innovative fuels (Pertalite RON 90/Pertamax Turbo RON 98) using the theory of Cognitive-Affective-Behavior (C-A-B). The study applies quantitative approach in investigating the relationships among the variables investigated, namely, cognitive (4Ps – product, price, place, promotion) and affective (satisfaction) that represent the independent variables, consumer’s environmental attitude the mediating variable, demographic factor the moderating variable and repeat purchase behaviour as the dependent variable. The results show direct positive relationship between Cognitive (product and prices) and environmental attitude as well as between Affective (satisfaction) and environmental attitude (Behavior). In addition, environmental attitude shows a direct positive relationship with repeat purchase (Behavior). Consumer’s environmental attitude is found to mediate the relationship between Cognitive (product and price) and repeat purchase; as well as on the relationship between Affective (satisfaction) and repeat purchase (Behavior).